Reflection of Political Law in the Development of State Constitution in Indonesia - Maghfira Nur Khaliza Fauzi (Fakultas Hukum Universitas Lampung, 2023)
The existence of goals in the state is in accordance with Emmanuel Kant's opinion that the existence of guarantees relating to the formation and defense is to improve the position of the law. There is a strong impetus that needs to be realized optimally when there is a change in the legal politics of state power, mainly so that there is no deviation from the direction of the law that will make it difficult to achieve the essence of the state. So how is the history related to the dynamics of legal politics in Indonesian state administration, political intervention in the development of Indonesian state administration, and finally how is the comparison of legal politics in national law and Islamic law. The problem approach used in this research is a normative approach. The normative approach is an approach that is carried out by collecting and studying applicable legal regulations that are closely related to research problems which include laws and regulations, official documents, and other sources. The results show that the reflection of the development or dynamics of legal politics in its influence on state administration includes the formation of laws and related authorities between each state institution, which is the basis for the direction of current state development. In this case, it is also seen that the role of legal politics can influence or intervene in the world of state administration, which is so dominating in various state administration structures. In this case, it is also necessary to see the role of legal politics in Islamic law, which is considered to play an important role historically in basic arrangements and is one of the factors in forming the pillars of state administration in Indonesia.